One-component bimolecular photoinitiating systems, 2 - Thioxanthone acetic acid derivatives as photoinitiators for free radical polymerization - Aydin, M; Arsu, N; Yagci, Y (WILEY-V C H VERLAG GMBH, 2003)
The compounds 2-thioxanthone-thioacetic acid and 2-(carboxymethoxy)thioxanthone, bimolecular photoinitiators for free radical polymerization, are synthesized and characterized. Their capability to act as initiators for the polymerization of methyl methacrylate was examined. The postulated mechanism is based on the intermolecular electron-transfer reaction of the excited photoinitiator with the sulfur or oxygen atom of the ground state of the respective photoinitiator followed by decarboxylation. The resulting alkyl radicals initiate the polymerization.
Keywords: electron transfer; initiators; photopolymerization; radical polymerization; thioxanthone; PHOTOSENSITIZED DECARBOXYLATION; CARBOXYLIC-ACIDS; Polymer Science